Proof of the Strength of the Relationship Between Pancasila Values and Citizenship - Anggun Paramitha (International Journal of Students Education, 2024)
The aim of this research is to prove the relationship that exists between Pancasila values in forming a sense of citizenship in teenagers. Teenagers are the future residents of a nation who are expected to embody the values of Pancasila in social life. These values are instilled through education at school and can lead to the creation of a sense of citizenship in teenagers. This research uses a literature review method. The data in this research was obtained through data collection techniques in the form of a framework, concept or orientation for analyzing or classifying facts collected in research conducted from reference sources (books, journals, papers). This research shows that there is a positive and significant correlation with all Pancasila values and a sense of citizenship, namely the first principle, second, third, fourth and fifth principles. Thus, the higher an individual's Pancasila value, the higher their sense of citizenship. It is hoped that the results of this research will provide a deeper understanding of the importance of Pancasila values in forming a strong and sustainable citizenship in Indonesia. In particular, the strongest relationships emerge from social justice and citizenship values.